Associations between conspiracism and the rejection of scientific innovations. (October 2021) - Marques, Mathew D.; Kerr, John R.; Williams, Matt N.; Ling, Mathew; McLennan, Jim
Public opinion regarding scientific developments such as genetically modified food can be mixed. We suggest such science-based technological innovations are rejected by some because they are perceived to be advanced as part of a conspiracy. In nationally representative samples (Australia n = 1011; New Zealand n = 754), we report the associations between five conspiracism facets and anti-science attitudes. Results indicate broad public opposition to genetically modified food and use of nuclear power, but more acceptance of renewable power, potable recycled water, 5G networks, and childhood vaccinations. There were small to moderate associations between the rejection of scientific innovations and conspiracism. Multivariate models estimating unique associations of conspiracism facets with anti-science attitudes suggested several novel and important relationships, particularly for childhood vaccination, genetically modified food, and 5G networks. We discuss the importance of examining factors such as conspiracism in understanding what may motivate and sustain rejection of scientific evidence-based claims about socially contentious technological innovations.